2011
DOI: 10.1371/journal.pbio.1001019
|View full text |Cite
|
Sign up to set email alerts
|

Nodal Dependent Differential Localisation of Dishevelled-2 Demarcates Regions of Differing Cell Behaviour in the Visceral Endoderm

Abstract: The anterior visceral endoderm (AVE), a signalling centre within the simple epithelium of the visceral endoderm (VE), is required for anterior-posterior axis specification in the mouse embryo. AVE cells migrate directionally within the VE, thereby properly positioning the future anterior of the embryo and orientating the primary body axis. AVE cells consistently come to an abrupt stop at the border between the anterior epiblast and extra-embryonic ectoderm, which represents an end-point to their proximal migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
93
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(100 citation statements)
references
References 46 publications
7
93
0
Order By: Relevance
“…This phenomenon is known as collective cell migration [1][2][3][4]. The unidirectional motion of cohesive cells contributes to the morphogenesis of multicellular organisms, for example in the left-right symmetry breaking of organs [5,6].…”
mentioning
confidence: 99%
“…This phenomenon is known as collective cell migration [1][2][3][4]. The unidirectional motion of cohesive cells contributes to the morphogenesis of multicellular organisms, for example in the left-right symmetry breaking of organs [5,6].…”
mentioning
confidence: 99%
“…6). A recent study (Trichas et al, 2011) has suggested that there are regional differences in F-actin and dishevelled 2 (Dvl2) protein localization between embryonic VE and extra-embryonic VE, and that these differences may explain why DVE cells do not pass the embryonic/extra-embryonic junction.…”
Section: Dve and Ave Migration: Driving Forces And Cellular Mechanismsmentioning
confidence: 99%
“…6). A recent study (Trichas et al, 2011) has suggested that there are regional differences in F-actin and dishevelled 2 (Dvl2) protein localization between embryonic VE and extra-embryonic VE, and that these differences may explain why DVE cells do not pass the embryonic/extra-embryonic junction.What might be the driving force of DVE cell migration? As the involvement of Rac1 and the WAVE complex suggests, time-lapse observations (Takaoka et al, 2011) have shown that DVE migration is an active and rapid process (it takes 5 hours for a DVE cell to move from the distal tip of the embryo to the embryonic/extra-embryonic junction).…”
mentioning
confidence: 99%
“…Hex-GFP (Rodriguez et al, 2001). This approach has demonstrated that DVE cells migrate while keeping epithelial integrity by intercalating between other VE cells (Migeotte et al, 2010;Srinivas et al, 2004;Trichas et al, 2011Trichas et al, , 2012. Moreover, cell tracking has shown that the whole VE layer is involved in a global reorganisation initiated by DVE motion (Rivera-Perez et al, 2003;Takaoka et al, 2011;Trichas et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This approach has demonstrated that DVE cells migrate while keeping epithelial integrity by intercalating between other VE cells (Migeotte et al, 2010;Srinivas et al, 2004;Trichas et al, 2011Trichas et al, , 2012. Moreover, cell tracking has shown that the whole VE layer is involved in a global reorganisation initiated by DVE motion (Rivera-Perez et al, 2003;Takaoka et al, 2011;Trichas et al, 2011). Detailed observation of DVE cells at the migration front revealed that they send long actin-dependent projections, which possibly sense the environment for orientation cues (Migeotte et al, 2010;Srinivas et al, 2004).…”
Section: Introductionmentioning
confidence: 99%